The Tradition of Ngunjung Buyut Ki Agus Jaka in Maintaining Religious Moderation of the Village Community - Alfarisi, Faqih; Rosyad, Rifki (Jurnal Iman dan Spiritualitas, 2024)
This study aims to analyze the role of local traditions in shaping cultural identity and maintaining the social balance of the community, with a case study on the Mapag Sri and Ngunjung Buyut Traditions in Serang Village, Cirebon Regency. This tradition is considered a form of respect for ancestors, as well as serving as a means of unifying the community. The research method used is descriptive-qualitative with an ethnographic approach, through field observations, interviews, and literature reviews. The results of the study show that the Ngunjung Buyut tradition, which involves respect for the Jaka Bagus figure, plays an important role in strengthening social bonds and maintaining local cultural values despite the adaptation to the times. This tradition is also seen as a medium to teach spiritual values, such as gratitude and respect for ancestors, which are combined with Islamic teachings through tawasul and tahlil processions. In conclusion, the Ngunjung Buyut tradition not only preserves cultural values but also maintains social harmony and adaptation to modern changes. The contribution of this research lies in a deeper understanding of the role of local traditions in maintaining cultural identity in the era of globalization.